2022
DOI: 10.1038/s41598-022-17933-2
|View full text |Cite
|
Sign up to set email alerts
|

Assessment, management, and incidence of neonatal jaundice in healthy neonates cared for in primary care: a prospective cohort study

Abstract: Jaundice caused by hyperbilirubinaemia is a common phenomenon during the neonatal period. Population-based studies evaluating assessment, management, and incidence of jaundice and need for phototherapy among otherwise healthy neonates are scarce. We prospectively explored these aspects in a primary care setting via assessing care as usual during the control phase of a stepped wedge cluster randomised controlled trial.We conducted a prospective cohort study embedded in the Screening and TreAtment to Reduce Seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 41 publications
1
3
0
1
Order By: Relevance
“…Instead, the evaluation of newborns heavily relies on HCWs' subjective assessments of the extent of 'yellowness' in the baby's skin. Similar ndings have been reported in a prospective cohort study of 860 Dutch newborns assessed in primary care birth centres (37). The research revealed that TcB or TSB measurements were not quanti ed in 44% of newborns considered 'quite yellow' and in 20% considered 'very yellow'.…”
Section: Discussionsupporting
confidence: 86%
“…Instead, the evaluation of newborns heavily relies on HCWs' subjective assessments of the extent of 'yellowness' in the baby's skin. Similar ndings have been reported in a prospective cohort study of 860 Dutch newborns assessed in primary care birth centres (37). The research revealed that TcB or TSB measurements were not quanti ed in 44% of newborns considered 'quite yellow' and in 20% considered 'very yellow'.…”
Section: Discussionsupporting
confidence: 86%
“…Participants were recruited while in the postpartum recovery ward to ensure that they received information on neonatal jaundice before they were discharged home as all of the women in the immediate postpartum are discharged through this ward. As neonatal jaundice commonly occurs in the first week of life [ 22 ], we delivered our intervention with in the first week post-delivery with three in four of all the mothers (73.4%) receiving the enhanced neonatal jaundice education intervention within 24 hours of giving birth. All women with live born infants including preterm and low birth weight babies were eligible for inclusion.…”
Section: Methodsmentioning
confidence: 99%
“…Neonatal hyperbilirubinemia (NHB) is the most common neonatal disease, with a prevalence rate of 20-40%, which is increasing year by year [ 1 ]. NHB threatens fetal health and increases the risk of long-term disease.…”
Section: Introductionmentioning
confidence: 99%